On the fine spectrum of the generalized difference operator B(r,s) over the sequence spaces c0 and c - Bilâl Altay; Feyzı Başar (International Journal of Mathematics and Mathematical Sciences)
We determine the fine spectrum of the generalized difference operator B(r,s) defined by a band matrix over the sequence spaces c0 and c, and derive a Mercerian theorem. This generalizes our earlier work (2004) for the difference operator Δ, and includes as other special cases the right shift and the Zweier matrices.